2018
DOI: 10.1111/rode.12537
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of entrepreneurship gender gaps: A cross‐country analysis

Abstract: This paper uses aggregate data from the International Labor Organization and microeconomic data from the European Values Study to study the empirical determinants of gender gaps in entrepreneurship, distinguishing between gender gaps in employership and in self-employment. Our sample of 44 countries consists mostly of European countries but varies broadly in terms of income level and institutional background since it includes both Western European countries and former Communist countries. In the aggregate data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…The negative sign in these coefficients can be interpreted as an indication that a person with a higher level of education will be less likely to engage in SE activities. In terms of the gender, the negative impact of higher education on female SE is slightly lower than the general population, yet higher than the impact on males, suggesting that females are less likely to engage SE males, confirming the results found in the existing SE literature (Cuberes et al 2019;Koellinger et al 2013;Simon and Way 2016). However, none of the changes due to the Crisis were significant except for college, where there was a reduction of the impact of education on SE by 1.06% for females, and a reduction of 1.5% males with college degree.…”
Section: Educationsupporting
confidence: 84%
“…The negative sign in these coefficients can be interpreted as an indication that a person with a higher level of education will be less likely to engage in SE activities. In terms of the gender, the negative impact of higher education on female SE is slightly lower than the general population, yet higher than the impact on males, suggesting that females are less likely to engage SE males, confirming the results found in the existing SE literature (Cuberes et al 2019;Koellinger et al 2013;Simon and Way 2016). However, none of the changes due to the Crisis were significant except for college, where there was a reduction of the impact of education on SE by 1.06% for females, and a reduction of 1.5% males with college degree.…”
Section: Educationsupporting
confidence: 84%
“…Others (Dilli and Westerhuis, 2018) discussed how gender plays a significant role in the business model selection of existing business or the strategy used by the entrepreneur (Kumar, 2013;Hodges et al, 2015;Eijdenberg et al, 2019). However, regarding new businesses, researchers discovered mixed results related to the gender effect on entrepreneurial intention (Malach-Pines and Schwartz, 2008;Cuberes et al, 2019). In general, a stream of research studied from different perspectives the role of gender within entrepreneurial activities affected by various environmental factors.…”
Section: Entrepreneurial Experience and Gender As Moderators For Entrepreneurial Marketing Strategy-business Performance And Institutionamentioning
confidence: 99%
“…This aspect is not only specific to the former communist countries, it is also a global one [81]. The conclusions of a study conducted by Cuberes et al [66] showed, following the example of 40 European countries, that the incidence of entrepreneurship is higher among men than among women. An analysis of Croatia's entrepreneurial profile compared to other post-socialist European countries showed that the chances of accessing entrepreneurship are higher for men than for women, and the likelihood of engaging in opportunity-based activities in a post-socialist context is more correlated with age than with gender and innovation [58].…”
Section: Gendermentioning
confidence: 97%
“…Ardagna and Lusardi [34] showed that entrepreneurs get help from their social networks whenever they need it, and the size of the network and the strength of the connection among members are essential for collecting the resources needed, and entrepreneurial success largely depends on the size and power of social networks [64]. The education in the field [11], promotes to increase in the entrepreneurial sector [65] and, especialy for women, the personal networks [66] are also important.…”
Section: Networkingmentioning
confidence: 99%